Not to Instantly Increase Manuscript Quantity, but to Accelerate Breakthroughs in Psychology: The Essence of Letter to the Editor (LtE): [Bukan Untuk Meningkatkan Kuantitas Naskah Secara Instan, Melainkan Mengakselerasi Terobosan di Bidang Ilmu Psikologi: Intisari Surat Kepada Editor] - Abraham, Juneman; Siaputra, Ide Bagus (Faculty of Psychology, Universitas Surabaya, 2023)
In the field of psychology, we witness and experience rapid development of ideas about humans, especially in the era of the Industrial Revolution 4.0, where psychology will accept the influence of cybernetic ideas. As a researcher in psychology who is diligent in observing human behavior, repeatedly in our minds, various